The Role of Substantive Understanding Approaches in The Changes of Fiqh - Firdaus, Firdaus; Azwar, Zainal (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aims to offer an approach in changing fiqh to stay in line with the demands of the texts and, at the same time, to create benefits for Muslims in their lives. This research is entirely library research whose data sources are obtained from several sources, including the Tarikh Tasyri Tasyri written by Khudari Bek, Tarikh al-Mazahib al-Islamiyyah fi Tarikh of al-Mazahib al-Fiqhiyyah written by Abu Zahrah, and al-Ittihad al-Fiqhiyyah inda Ashab al-Hadis fi al-Qarni al-Tsalits al-Hijri by Abd al-Majid Mahmud Abd al-Majid, and several other sources relevant to the topic studied. The analysis technique used is content analysis, which is the only technique used in analyzing the information process. This research finds the fact that fiqh changes are a necessity to respond the social development as well as to create benefit for society. Efforts to change fiqh can be done by using a substantive understanding of the syara 'texts which are the basis and source of change. It is in these aspects does appear the importance of the role of substantive understanding in the process of legal changes, as a solution in responding to the current and future development of society.